Novel Pyroptosis-Related Gene Signatures Identified as the Prognostic Biomarkers for Bladder Carcinoma - You, Jia; Li, Huawei; Wei, Yuanfeng; Fan, Peng; Zhao, Yaqin; Yi, Cheng; Guo, Qing; Yang, Xi (Frontiers in Oncology, 2022)
Background: Bladder carcinoma (BLCA) is a common malignant tumor with high morbidity and mortality in the urinary system. Pyroptosis is a pattern of programmed cell death that is closely associated with progression of tumors. Therefore, it is significant to probe the expression of pyroptosis-related genes (PRGs) in BLCA. Methods: The differentially expressed genes in normal and BLCA tissues were first gained from the Cancer Genome Atlas (TCGA) database analysis, as well as PRGs from National Center for Biotechnology Information (NCBI) database, intersecting to obtain Differentially Expressed Pyroptosis-Related Genes (DEPRGs) in BLCA. With the construction of a prognostic model of pyroptosis by regression analysis, we derived and validated key genes, which were ascertained as a separate prognostic marker by individuation prognostic and clinical relevance analysis. In addition, we gained six immune cells from the Tumor Immune Evaluation Resource (TIMER) website and analyzed the relationship between pyroptosis prognostic genes and immune infiltration. Result: Our result gained that 31 DEPRGs were available by comparing normal and BLCA tissues with |log2 (Fold Change, FC)|>0.5 and FDR <0.05. And four key genes (CRTAC1, GSDMB, AIM2 and FOXO3) derived from the pyroptosis prognostic model were experimentally validated for consistent expression in BLCA patients. Following risk scoring, the low-risk group of BLCA patients had noticeably higher overall survival (OS) than the high-risk group (P < 0.001). And, risk score was still an independent prognostic factor (HR = 1.728, 95% CI =1.289–2.315, P < 0.001). We found remarkable correlations among the expression of pyroptosis-related prognostic genes and the immune infiltration of CD4+T cells, CD8+T cells, B cells, dendritic cells, macrophages, and neutrophils. Conclusion: Genes (CRTAC1, GSDMB, AIM2 and FOXO3) associated with pyroptosis are potential BLCA prognostic biomarkers that act as an essential part in the predictive prognosis of survival and immunotherapy of BLCA.